Autoantibody Response to Murine Double Minute 2 Protein in Immunodiagnosis of Hepatocellular Carcinoma - Mei Liu; Su-jun Zheng; Yu Chen; Ning Li; Peng-fei Ren; Li-ping Dai; Zhong-ping Duan; Jian-Ying Zhang (Journal of Immunology Research)
Hepatocellular carcinoma (HCC) is the fifth most common malignancy worldwide. Although new therapeutic strategies have been continuously developed and applied to clinical treatment for HCC, the prognosis is still very poor. Thus, early detection of HCC may enhance effective and curative management. In this study, autoantibody responses to MDM2 protein in HCC patient’s serum were evaluated by enzyme-linked immunosorbent assay (ELISA) and part sera were evaluated by Western blotting and indirect immunofluorescence assay. Immunohistochemistry (IHC) over tissue array slides was also performed to analyze protein expression of MDM2 in HCC and control tissues. The prevalence of autoantibodies against MDM2 was significantly higher than that in liver cirrhosis (LC), chronic hepatitis (CH), and normal human sera (NHS). The average titer of autoantibodies against MDM2 in HCC serum was higher compared to that in LC, CH, and NHS. A high titer of autoantibodies against MDM2 in ELISA could be observed in the serum in 6 to 9 months before the clinical diagnosis of HCC in the serum of several HCC patients with serial bleeding samples. Our preliminary data indicate that MDM2 and anti-MDM2 system may be a potential biomarker for early stage HCC screening and immunodiagnosis.